Windows of Sensitivity to Toxic Chemicals in the Development of Cleft Palates - Buser, M. C. (J Toxicol Environ Health B Crit Rev, 2015)
Cleft lip and cleft palate are among the most common birth defects worldwide. There is a genetic component to the development of these malformations, as well as evidence that environmental exposures and prescription drug use may exacerbate or even produce these manifestations. Thus, it is important to understand the underlying mechanisms and when these exposures affect development of the growing fetus. The purpose of this investigation was to critically review the available literature related to orofacial cleft formation following chemical exposure and identify specific time frames for windows of sensitivity. Further, an aim was to evaluate the potential for predicting effects in humans based on animal studies. Evidence indicates that chemical causes of cleft palate development are due to dose and timing of exposure, susceptibility of the species (i.e., the genetic makeup), and mechanism of action. Several studies demonstrated that dose is a crucial factor; however, some investigators argued that even more important than dose was timing of exposure. Data show that the window of sensitivity to environmental teratogens in the development of cleft palates is quite narrow and follows closely the window of palatogenesis in the fetus of any given species.